PENGARUH DEWAN PENGAWAS SYARIAH DAN KOMITE AUDIT TERHADAP KINERJA PERBANKAN SYARIAH (STUDI PADA BANK NTB SYARIAH) - Anwar Musaddad (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
This research discusses the influence of the Sharia Supervisory Board (DPS) and the Audit Committee on the performance of Islamic banking in a case study at Bank NTB Syariah. This research is a descriptive study using multiple regression analysis method and processed using SPSS version 16. Based on the results of the study it was concluded that partially the Sharia Supervisory Board (X1) had a significant influence on Islamic banking performance with a significance value of 0.05. Meanwhile, the Audit Committee (X2) has no significant effect on the performance of Islamic banking. Meanwhile, the Sharia Supervisory Board (X1) and the Audit Committee (X2) simultaneously have a significant relationship with Islamic banking performance.